Determinantes da demanda e da utilização de crédito rural por produtores de bovinos de corte no estado de São Paulo - Carrer, Marcelo José (2012)
The present study aims to identify determinants of the decision of beef cattle farmers on whether or not to demand rural credit. The specific purposes are: i) identify barriers to the rural credit demand by beef cattle farmers in the state of Sao Paulo; ii) identify determinants of adoption of different rural credit contracts by beef cattle farmers and; iii) identify determinants of the volume of rural credit used by beef cattle farmers. The sample comprises data on 86 livestock farmers in 10 regions of São Paulo State. The empirical analysis of the survey data is performed with the estimation of a logit model and with descriptive statistics. The theoretical framework used was the New Institutional Economics applied to the context of rural credit markets, with main focus on screening, monitoring and enforcement problems of rural credit contracts. The results show that all farmers who demanded credit in 2010 had access to it. However, the bureaucracy (which increases transaction costs) inherent in the process of obtaining credit and the fear of losing the collateral has been identified as mechanisms of selfselection and therefore self-exclusion from the process of farmers demand for rural credit. In the logit model results was found that farmers who adopted capital intensive production systems, have off-farm income, have more than one farm, are younger and are affiliated to producers association linked to livestock are more likely to demand rural credit. Some of these variables, such as greater number of farms and income from off-farm activities may present distortions in rural credit policy for beef cattle in São Paulo. Resources under special conditions from the governmental rural credit program may be coming at the hands of farmers who least need these resources. To identify the determinants of the expansion of access and use of rural credit by farmers were also used a logit model. The results showed that farmers who adopted capital intensive production systems, have more farms, are older and adopt risk management mechanisms are more likely to use two or more rural credit contracts. These farmers have adopted different strategies to overcome the volume limits of governmental rural credit, which were presented in the study. We concluded that the relaxation of requirements for obtaining rural credit is not the best mechanism to increase demand and use of rural credit by beef cattle farmers. On the contrary, the relaxation of conditions of access to rural credit can make the results of the rural credit policy disastrous in terms of default and financial sustainability. Last but not least, some suggestions were presented for beef cattle rural credit policy in the State of São Paulo. These suggestions are grounded in the results of econometric models presented here and go beyond the rural credit market itself.